Characteristics of Water Consumption in Chocianów, Parchów and Pogorzeliska, Lower Silesia Province - Ogiołda, Ewa; Nowogoński, Ireneusz; Pietrzak, Przemysław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Water consumption is an amount characteristic to individual water sup-ply systems. It is described by values of the unitary consumption of water and unevenness coefficients. An analysis of consumption for the years 2009-2016 in two systems which are diverse in terms of the number of supplied recipients as well as the intended water use is presented.
Keywords: water supply system; water consumption; irregularity of water consumption; sieć wodociągowa; zużycie wody; nieregularność zużycia wody